(untitled) (The Pakistan Development Review, 1994)
Pakistan, with an estimated population of 122 million in 1993, is the eighth most populous country in the world. The historical trends indicate a continuous and exponentially increasing growth in population because of sustained high fertility and declining mortality. Currently, the population is growing at around 3 percent per annum, one of the highest rates of growth in the world. In Pakistan, the contraceptive prevalence is very low (14 percent) and the fertility level is among the highest in the world. There has been only a marginal decline in fertility in Pakistan over the last two decades. An average married woman in Pakistan still experiences a total of at least seven children if she survives and completes her reproductive period. Using data from the Pakistan Contraceptive Prevalence Survey 1984-85 [see Population Welfare Division, (1986) for details], the purpose of this analysis is to determine whether there are any differentials in fertility levels by age at marriage, educational level, work status, region of residence (province), and place of residence (urban or rural). Both bivariate and multivariate analyses have been undertaken to examine the effects of these demographic andsocio-economic factors on the level of fertility.